2016
DOI: 10.1590/0004-282x20160152
|View full text |Cite
|
Sign up to set email alerts
|

Simple prediction model for unfavorable outcome in ischemic stroke after intravenous thrombolytic therapy

Abstract: Stroke is one of the leading causes of morbidity and mortality worldwide, and since the approval of intravenous thrombolysis (IVT) with recombinant tissue plasminogen activator (rtPA, alteplase) in 1996 1 as a treatment option, acute stroke management has experienced a paradigm shift. Focus has moved to prompt and accurate diagnosis followed by time-sensitive administration of a therapy that effectively and safely restores blood flow to the affected vascular territory.Unfortunately, not all patients improve wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
(13 reference statements)
2
16
0
Order By: Relevance
“…In a study that that included 82 patients with acute ischemic stroke treated with thrombolytic therapy, found that NIHSS score > 12 on arrival, age > 70 years and the presence of hyperdense artery sign (according to ASPE CT assessment) are predictors of unfavourable outcome Fig. 1 Evolution of NIHSS from admission to the evaluation at 7 days at 3 months [27]. According to our findings, we observed that increased initial ASPECTS score was associated with better outcomes.…”
Section: Discussionsupporting
confidence: 62%
“…In a study that that included 82 patients with acute ischemic stroke treated with thrombolytic therapy, found that NIHSS score > 12 on arrival, age > 70 years and the presence of hyperdense artery sign (according to ASPE CT assessment) are predictors of unfavourable outcome Fig. 1 Evolution of NIHSS from admission to the evaluation at 7 days at 3 months [27]. According to our findings, we observed that increased initial ASPECTS score was associated with better outcomes.…”
Section: Discussionsupporting
confidence: 62%
“…We found that patients with hyperdense middle cerebral artery (HMCA) and those with a large-sized infarction had unfavorable outcomes; however, the association did not reach significance. HMCA sign has been recorded as a factor of a high incidence of unfavorable outcome [33] and used as an item of thrombotic stroke instrument designed to predict poor outcomes [34]. A recent meta-analysis [35] found that patients with an initial HMCAS were 1.56-fold more likely to have unfavorable outcomes than those who did not present with this sign.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have predicted the outcome of AIS patients using only one or two factors, particularly the NIHSS score and age, which have been recognized as the most direct contributors to patient outcome (20). The NIHSS score indicates the degree of neurological function damage and is frequently used to determine the severity of the patient's condition on admission (21).…”
Section: Discussionmentioning
confidence: 99%